2022
DOI: 10.3389/fpsyg.2022.942520
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neuroticism and mobile phone use among college students in love: The masking effect of self-emotional assessment

Abstract: The relationship between neuroticism and mobile phone use is a hot research topic in the academic community. The purpose of this study was to investigate the roles of self-emotional assessment and love status in the mechanism through which college students’ neuroticism influences mobile phone use.We construct a moderated mediation model, and taking 869 Chinese college students as the research object and testing the mediating role of self-emotional assessment and the moderating role of love status. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Neurotic people are defined as rather emotionally unstable, impulsive people, who tend to get angry fast and perceive life negatively [ 37 ]. Other studies have found that neuroticism is significantly positively related to higher smartphone [ 22 ] and social media usage [ 38 ] or even to a smartphone addiction [ 39 , 40 ]. While more neurotic users use their phone more, their IDL was higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotic people are defined as rather emotionally unstable, impulsive people, who tend to get angry fast and perceive life negatively [ 37 ]. Other studies have found that neuroticism is significantly positively related to higher smartphone [ 22 ] and social media usage [ 38 ] or even to a smartphone addiction [ 39 , 40 ]. While more neurotic users use their phone more, their IDL was higher.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ], for example, found an association between call durations and the number of notifications per day as well as the level of extraversion. Other personality traits, like neuroticism, are also positively related to smartphone usage [ 22 ]. In addition to personality traits, ref.…”
Section: Related Workmentioning
confidence: 99%